2017
DOI: 10.1097/ta.0000000000001341
|View full text |Cite
|
Sign up to set email alerts
|

Review of military and civilian trauma registries

Abstract: Well-established and reliable trauma registries and databases are fundamental in (military) trauma care. We recommend implementation of a (concurrent) UN/NATO wide registry system with a track and follow-up system to further improve the quality of care and registration of casualties. Further research should focus on real time aids available on the battlefield and direct storage/upload in trauma databases in theater. Ultimately, sound and valid data support medical decision process and evaluation necessary to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
7
0
1
Order By: Relevance
“…The expert panel agreed that there should be an international collaboration to record these data, both for patient case history and for process improvement, and to capture lessons learned. This supports the previous recommendation of Van Dongen et al 21 to implement a United Nations/NATO wide registry system for further improvement of CCC and the registration of casualties. The concept of an international registry has already been proven feasible in a civilian setting 27 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The expert panel agreed that there should be an international collaboration to record these data, both for patient case history and for process improvement, and to capture lessons learned. This supports the previous recommendation of Van Dongen et al 21 to implement a United Nations/NATO wide registry system for further improvement of CCC and the registration of casualties. The concept of an international registry has already been proven feasible in a civilian setting 27 .…”
Section: Discussionsupporting
confidence: 90%
“…Hence, essential information might be missing from current analyses. Furthermore, as the current study demonstrates, specific data on bleeding control measures for truncal and junctional hemorrhage is often not extensively captured in present registries 20,21 . The JTS does have a process to collect comprehensive REBOA data for process improvement, but data on other ABC modalities are not registered in such detail 4,26 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Further obvious differences exist also between civilian and military registries, making comparison difficult if not impossible. Van Dongen et al identified 203 key variables fundamental for the implementation of an effective military trauma registry [11]. Expectedly, data available from the Iliad-both direct and extrapolated-are nowhere near those needed for a modern trauma registry; other than the names and the affiliation of the opponents, only five variables could be collected for the majority of cases (type of weapon, mechanism of injury, body area, NISS and outcome), but the overall methodology can be applied.…”
Section: Discussionmentioning
confidence: 99%